2011
DOI: 10.3109/17435390.2010.541604
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory responses of RAW 264.7 macrophages upon exposure to nanoparticles: Role of ROS-NFκB signaling pathway

Abstract: Recent advances in particle-forming chemistries used for developing nanotechnology has not only widened novel applications for nanoscale materials but also has provided significant concern regarding their biological effects. The present study investigates the inflammatory responses of RAW 264.7 mouse macrophages exposed to nanoparticles (NPs, 5 μg/ml) of varied sizes including silver (Ag), aluminum (Al), carbon black (CB), carbon-coated silver (CAg) and gold (Au). A significant increase in IL-6, reactive oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
122
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(133 citation statements)
references
References 43 publications
7
122
0
2
Order By: Relevance
“…The proinflammatory cascade returned to normal after the subchronic exposure of GNPs (Figure 1). Nishanth et al (2011) observed significant induction of IL-6 and TNF-α in mouse macrophages by silver nanoparticles followed by aluminum, carbon black and carbon-coated silver nanoparticles; however, no such prominent proinflammatory responses were observed with GNPs, suggesting their biocompatibility. The results of another in vitro study on murine macrophages has suggested that 60 nm GNPs are not cytotoxic or do not elicit proinflammatory (IL-6, TNF-α) responses (Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 86%
“…The proinflammatory cascade returned to normal after the subchronic exposure of GNPs (Figure 1). Nishanth et al (2011) observed significant induction of IL-6 and TNF-α in mouse macrophages by silver nanoparticles followed by aluminum, carbon black and carbon-coated silver nanoparticles; however, no such prominent proinflammatory responses were observed with GNPs, suggesting their biocompatibility. The results of another in vitro study on murine macrophages has suggested that 60 nm GNPs are not cytotoxic or do not elicit proinflammatory (IL-6, TNF-α) responses (Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 86%
“…Studies using various cell lines reported that Ag-NPs affected mitochondrial function and induced cell necrosis or apoptosis 24,25) . However, other investigators found no such cytotoxic effects of Ag-NPs on living cells 26) .…”
Section: Discussionmentioning
confidence: 99%
“…their size, size distribution, shape, state of dispersion, physical and chemical properties, surface area and porosity, surface chemistry) and by cell characteristics (e.g. cell line, number of cells per well, and the period of culture before and/or after exposure to nanoparticles) 17,[24][25][26]29,30) . A recent study showed a decrease in MC3T3-E1 cell viability after exposure to Ag-NPs using the WST-8 assay 31) , but this study used different test conditions for cell culture and exposure to Ag-NPs, which may explain the disparity between their results and ours.…”
Section: Discussionmentioning
confidence: 99%
“…37 Signaling pathways, such as PI3K-AKT, 38 NFκB, 39 and EGFR, 40 have been reported as key signaling pathways influenced by NPs. In a recent study, silver NPs with positive and negative charges were used to study gene expression related to oxidative stress, and the results showed that the gene-expression pattern did not differ with surface charge.…”
Section: Discussionmentioning
confidence: 99%